ANALYSIS OF SAFETY ISSUE OF POTHOLES AND LIGHTING: CASE A JALAN BEBER – JATIWANGI, MAJALENGKA - Yoga Setyawan; Yusra Aulia Sari (LEADER: Civil Engineering and Architecture Journal, 2024)
Autonomous driving is currently one of the major trends in the automotive industry. As the technical implementation of highly automated driving or his SAE level of automation draws closer and closer, attention is now shifting from mere feasibility to the question of how acceptable driving styles, and therefore comfort, can be implemented. [1] A global issue that requires urgent and careful consideration is that of travel safety. Roads are infrastructure that have a major impact on people's daily lives and represent important connections between regions. In addition to displaying a route to guide the driver, it also has the ability to remove obstacles. Therefore, healthy road conditions play an important role in promoting various aspects of communication, making visual observation more comfortable, and increasing the efficiency and effectiveness of activities. Because good road conditions make any activity on the road easier, drivers feel more comfortable, and their activities are more effective and efficient. His two biggest problems facing developed countries in Asia are the lack of proper lighting and the increase in potholes. This frightening scenario has far-reaching implications, especially for driver safety and health. Additionally, this negatively affects driver reaction, making potholes difficult to detect and increasing the likelihood of a collision. This can lead to physical and internal destruction of the road and also endanger the safety of road users. In recent years, road construction has increased significantly, requiring roads to be in good condition. When pavements are stressed by heavy traffic or climate change, their behavior and condition change. Cracking is the most common problem occurring in the pavement sector in Malaysia [2]. To understand and address this problem, it is essential to study how drivers react to potholes and poor street lighting in Asia. The Indonesian government also faces serious difficulties in this regard. Poor infrastructure has a negative impact on the economy. In the context of a developing country like Indonesia, the government could minimize the severity of road accidents by providing street lighting and road repairs. surface. Using traffic accident data from the Republic of Indonesia Police Traffic Control Center and a negative binomial regression method, street lighting and road surface improvements are associated with a 4.2% and 3.4% reduction in traffic fatalities and injuries, respectively. I understand that. 3]. However, minimal lighting makes it difficult for drivers to react to changing road conditions. To overcome the problems of potholes and insufficient lighting on Majalenka roads, this study aims to generate concrete recommendations that will guide the development of future road infrastructure and lighting technologies. Street lighting and road surface improvements also have an impact on reducing traffic fatalities. Street lighting is very important for motorists, especially to prevent accidents, reduce crime rates, and provide illumination that resembles everyday objects. In addition, street lights also serve as navigation aids for drivers at night. Street lights reduce the number of accidents. After studying 62 street lighting and accident data from 15 countries, we can conclude that street lighting reduces accidents by an average of 30%. Includes all roads, highways, intersections, and junctions [4]. Beber Jatiwangi is a village in Ligun, Majalengka region. Located in Majalengka, in the middle of the Ligun factory area, this issue is widely discussed in the local community as it affects industrial activities. As a result, impacts include damage to logistics vehicles and an increased risk of accidents.